Down-Regulation of Essential Synaptic Components by GI-Tract Microbiome-Derived Lipopolysaccharide (LPS) in LPS-Treated Human Neuronal-Glial (HNG) Cells in Primary Culture: Relevance to Alzheimer’s Disease (AD) - Zhao, Yuhai; Sharfman, Nathan M.; Jaber, Vivian R.; Lukiw, Walter J. (Frontiers in Cellular Neuroscience, 2019)
Trans-synaptic neurotransmission of both electrical and neurochemical information in the central nervous system (CNS) is achieved through a highly interactive network of neuron-specific synaptic proteins that include pre-synaptic and post-synaptic elements. These elements include a family of several well-characterized integral- and trans-membrane synaptic core proteins necessary for the efficient operation of this complex signaling network, and include the pre-synaptic proteins: (i) neurexin-1 (NRXN-1); (ii) the synaptosomal-associated phosphoprotein-25 (SNAP-25); (iii) the phosphoprotein synapsin-2 (SYN-2); and the post-synaptic elements: (iv) neuroligin (NLGN), a critical cell adhesion protein; and (v) the SH3-ankyrin repeat domain, proline-rich cytoskeletal scaffolding protein SHANK3. All five of these pre- and post-synaptic proteins have been found to be significantly down-regulated in primary human neuronal-glial (HNG) cell co-cultures after exposure to Bacteroides fragilis lipopolysaccharide (BF-LPS). Interestingly, LPS has also been reported to be abundant in Alzheimer’s disease (AD) affected brain cells where there are significant deficits in this same family of synaptic components. This “Perspectives” paper will review current research progress and discuss the latest findings in this research area. Overall these experimental results provide evidence (i) that gastrointestinal (GI) tract-derived Gram-negative bacterial exudates such as BF-LPS express their neurotoxicity in the CNS in part through the directed down-regulation of neuron-specific neurofilaments and synaptic signaling proteins; and (ii) that this may explain the significant alterations in immune-responses and cognitive deficits observed after bacterial-derived LPS exposure to the human CNS.